Effect of Regulated Deficit Irrigation on Cucumber Growth and Fruit Yield in Greenhouse Conditions - Khan, Muhammad Mumtaz; Al-Subhi, Saleem Juma; Akram, Muhammad Tahir; Al-Busaidi, Waleed; Siddiqi, Sajjad Ahmad; Farooque, Aitazaz A. (AGRIVITA Journal of Agricultural Science, 2024)
Water scarcity is an extreme global concern due to changing climate and rapid population growth. Worldwide, freshwater sources are depleting and there is a need to implement water-conserving approaches in water-limited or arid areas for sustainable crop production. Therefore, this study aimed to investigate the impact of deficit irrigation on cucumber plant physiology, growth, and fruit yield traits grown under greenhouse conditions. The experiment was conducted in a complete randomized design with four water regimes, 100%, 80%, 60%, and 40% crop water requirement (ETc). Results showed that the highest plant leaf chlorophyll contents (43.2 µmol m-2), plant biomass (12.43 g), plant height (172.39 cm), number of leaves (19.85), fruit yield (2.49 kg), and total soluble solids (3.73 °Brix) were in plants irrigated at 100% level. In comparison, the lowest plant height (115.73 cm), number of leaves (15.77) and fruit yield (1.81 kg) were recorded at 40% irrigation. Results revealed that reduced irrigation regimes up to 80% or 60% have no significant inhibitory effects on cucumber agro-morphological traits. However, 40% of irrigation levels showed significantly reduced plant morphological and fruit yield traits. Overall, the result demonstrated that regulated deficit irrigation can significantly conserve water without negatively impacting cucumber yield.